Kitab Undang-Undang Fikih Jinayah (KUFJ) - Gunawan, Hendra (IAIN Padangsidimpuan, 2017)
This article discusses the Jinayah Jurisprudence Act (KUFJ), so the main problem in this article is whether there is a Criminal Code (KUHP) version of Islamic law, and how Islamic law responds to all crimes that occur in society begin then until now. From this problem the author tries to trace the books of fiqh which regulate criminal acts of crime, especially from jinayah fiqh books. The method used in the preparation of this article is descriptive qualitative sourced from fiqh books and books relating to the topics discussed in this article, the method of collecting literature study data by trying to codify the rules of Jurisprudence that have been described by fiqh scholars in different books and books.findings of the authors in this article, that all forms of previous criminal offenses up to the new model criminal offenses that emerged in the naw era, are in fact far summarized in the great constitution of Muslims (al-Qur'an). Only the question regarding criminals is that there is no book that summarizes in detail such as the Criminal Code in force in Indonesia at this time. But if you look closely, the Koran actually regulates all types and modes of crime that are just emerging now. So in this article the author tries to describe the Criminal Code a la jihay in the following discussion.